Clearance of Mycoplasma genitalium and Trichomonas vaginalis Among Adolescents and Young Adults With Pelvic Inflammatory Disease: Results From the Tech-N Study. Issue 11 (November 2020) - Trent, Maria; Yusuf, Hasiya E.; Perin, Jamie; Anders, Jennifer; Chung, Shang-en; Tabacco-Saeed, Lisa; Rowell, Julia; Huettner, Steven; Rothman, Richard; Butz, Arlene; Gaydos, Charlotte A.
Abstract : Abstract: Current pelvic inflammatory disease (PID) treatment effectively treats Neisseria gonorrhoeae (NG) and Chlamydia trachomatis (CT). However, coverage may be inadequate for Mycoplasma genitalium (MG)/ Trichomonas vaginalis (TV) infections. We compared the longitudinal MG and TV outcomes with NG/CT outcomes for women enrolled in a longitudinal randomized controlled trial to optimize outcomes after PID. The prevalences of CT and NG were lower at 30- and 90-day follow-up compared with the prevalence at the time of diagnosis. No significant difference was observed for MG (odds ratio, 0.95; 0.86–1.04; P = 0.265) and TV (odds ratio, 0.89; 0.75–1.04; P = 0.146) over time for both treatment groups, showing that persistence and/or reinfection with MG and TV occurs more frequently than with CT or NG after treatment of PID using current national treatment guidelines. Abstract : In our study of 286 women with a diagnosis of PID, there was no statistically significant change in Mycoplasma genitalium and Trichomonas vaginalis prevalence at 30- and 90-day follow-up.